(untitled) (ENTHYMEMA, 2019)
Presentazione della sezione “«We Should Never Write Without Feelings». Studi su William T. Vollmann”. Introduction to the monographic section “’We Should Never Write Without Feelings.’ Studies on William T. Vollmann”.